2005
DOI: 10.2174/1381612054367283
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Vascular Genes by Glucose

Abstract: Endothelial dysfunction is an early sign of diabetic vascular disease. Due to their unique position at the border between blood and vascular tissue, endothelial cells (EC) are the first vascular cells to sensor humoral changes, and they are able to transmit the information about these changes to other vascular cell types by changing their gene expression profile and producing growth factors, cytokines, adhesion molecules, and other bioactive molecules. These signals alter vascular cell dynamics and interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 173 publications
1
19
1
Order By: Relevance
“…The downregulation of GLUT1 expression in diabetic animals has been shown in the retina but not the cerebrum (Fernandes et al, 2004;Badr et al, 2000). Although chronic hyperglycemia is known to affect gene expression in a number of tissues and cells (Stenina, 2005), the alteration of GLUT-1 mRNA levels was not involved in the downregulation of GLUT-1 protein in the present study. These results are consistent with a study that reported that high glucose did not affect GLUT1 mRNA levels in bovine RPE cells (Fernandes et al, 2004).…”
Section: Discussioncontrasting
confidence: 43%
“…The downregulation of GLUT1 expression in diabetic animals has been shown in the retina but not the cerebrum (Fernandes et al, 2004;Badr et al, 2000). Although chronic hyperglycemia is known to affect gene expression in a number of tissues and cells (Stenina, 2005), the alteration of GLUT-1 mRNA levels was not involved in the downregulation of GLUT-1 protein in the present study. These results are consistent with a study that reported that high glucose did not affect GLUT1 mRNA levels in bovine RPE cells (Fernandes et al, 2004).…”
Section: Discussioncontrasting
confidence: 43%
“…In contrast, type 1 diabetic individuals (the remaining 5%) typically show no signs of metabolic syndrome and have low levels of insulin due to the destruction of pancreatic beta cells. Both, glucose and insulin have been implicated in gene regulation that may promote the development of cardiovascular disease in diabetic patients [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…In vascular cells, glucose regulates expression of many genes that have been linked to the development of atherosclerosis or abnormal angiogenesis (reviewed in Ref. 7). One of them is thrombospondin-1 (TSP-1), 3 a cell matrix protein implicated in both atherogenesis (8 -12) and angiogenesis (13)(14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%